PROP1 overexpression in corticotrophinomas: evidence for the role of PROP1 in the maintenance of cells committed to corticotrophic differentiation (Clinics, 2013)
OBJECTIVE: The expression of transcription factors involved in early pituitary development, such as PROP1 and POU1F1, has been detected in pituitary adenoma tissues. In this study, we sought to characterize the transcriptional profiles of PROP1, POU1F1, and TBX19 in functioning and nonfunctioning pituitary adenomas in an attempt to identify their roles in tumorigenesis and hormone hypersecretion. METHODS: RT-qPCR analyses were performed to assess the transcriptional pattern of PROP1, POU1F1, TBX19, and hormone-producing genes in tissue samples of corticotrophinomas (n = 10), somatotrophinomas (n = 8), and nonfunctioning adenomas (n = 6). RESULTS: Compared with normal pituitary tissue, POU1F1 was overexpressed in somatotrophinomas by 3-fold. PROP1 expression was 18-fold higher in corticotrophinomas, 10-fold higher in somatotrophinomas, and 3-fold higher in nonfunctioning adenomas. TBX19 expression was 27-fold higher in corticotrophinomas. Additionally, the level of TBX19 mRNA positively correlated with that of pro-opiomelanocortin (r = 0.49, p = 0.014). CONCLUSIONS: Our data demonstrate that PROP1 is overexpressed in pituitary adenomas, mainly in corticotrophinomas. Together with previously published data showing that patients who harbor PROP1 loss-of-function mutations present a progressive decline in corticotrope function, our results support a role for PROP1 in pituitary tumor development and in the maintenance of cell lineages committed to corticotrophic differentiation.